2014
DOI: 10.1155/2014/903452
|View full text |Cite
|
Sign up to set email alerts
|

Humoral and Haemocytic Responses ofLitopenaeus vannameito Cd Exposure

Abstract: White shrimp, Litopenaeus vannamei, subadults were exposed to four dilutions of the 96 h cadmium LC50 reported for postlarvae (PL12) of this species, and the effects were evaluated after 5, 48, and 96 h of exposure. While treatments did not affect survival and hemolymph clotting time increased with time, but not as a response to Cd exposure, the intensity of other responses was related to concentration, to time of exposure, and to their interaction. Hemocyanin decreased with time in all metal concentrations bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…6 and Supplementary Tables S2 , S3 , S8 ). The expression of prophenoloxidase and acid phosphatase ( ACP ) were significantly down-regulated ( Supplementary Tables S2 , S3 ), supporting previously biochemical observations that phenoloxidase activity was reduced by Cd and nickel in Litopenaeus vannamei 45 and Scylla serrata 46 respectively, and the activity of the ACP was decreased by Cu in the hepatopancreas of M. rosenbergii 47 . Moreover, as shown in Fig.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…6 and Supplementary Tables S2 , S3 , S8 ). The expression of prophenoloxidase and acid phosphatase ( ACP ) were significantly down-regulated ( Supplementary Tables S2 , S3 ), supporting previously biochemical observations that phenoloxidase activity was reduced by Cd and nickel in Litopenaeus vannamei 45 and Scylla serrata 46 respectively, and the activity of the ACP was decreased by Cu in the hepatopancreas of M. rosenbergii 47 . Moreover, as shown in Fig.…”
Section: Discussionsupporting
confidence: 84%
“…Lectin, cathepsin L and other enzymes in lysosome have been reported to involve and enhance the function of phagocytosis 17 22 43 44 . In our expression profile analyses, cathepsin L , lysozyme , c-type lectin , c-type lectin receptor and GILT were revealed to be significantly up-regulated and enriched when crabs were exposed to Cd ( Figs 4 , 5 , 6 , and Supplementary Tables S2 , S4 , S8 ), suggesting that phagocytosis activity might be induced to remove and clear damaged cells and macromolecules 11 17 45 46 . In contrast, numbers of immune-related genes were down-regulated after Cd exposure ( Fig.…”
Section: Discussionmentioning
confidence: 91%
“…The rest had intermediate values and, as was the case with hemocyanin, there were no significant differences between the final values of the control and those obtained with the different concentrations of Cu (Table 5(A)). In a similar study, Bautista-Covarrubias et al (2014) determined that exposure of L. vannamei juveniles for 96 h to Cd concentrations equitoxic to those of Cu used in this study (1, 10, and 50% the LC 50-96 h) caused significant decreases of hemocyte concentrations and PO activity. Since part of the defensive role of hemocytes is the release of the proPO-activating system from storage granules (Johansson et al 2000), PO to hemocyte ratios were higher with increasing Cd.…”
Section: Resultsmentioning
confidence: 71%
“…In L. vannamei exposed to metals, Bautista‐Covarrubias et al () reported a decrease in the proPO as an initial response (when exposed to Cd), but no observed in those exposed to Cu; indicating the metal‐specific response in this decapod. In the present study, the organisms exposed to sublethal metal concentrations apparently did not lose homeostasis, however when interacting with the pathogen, the indicators of immunological responses were affected.…”
Section: Discussionmentioning
confidence: 89%
“…A significant THC reduction has been reported in WSSV‐infected shrimp (Wang et al, ). In L. vannamei juveniles exposed to Cd, Bautista‐Covarrubias et al () reported a decrease in the THC values, although this relation was not observed when exposed to Cu (Bautista‐Covarrubias et al, ). In the present study, the severe decrease of hemocyte concentrations in the WS and WS‐MM treatments during the third day of exposure might be explained by hemocyte migration as described in the case of severely infected or damaged tissues and organs (van de Braak, Botterblom, Huisman, Rombout, & van der Knaap, ; Vafopoulou, ), increasing the effect due to a possible synergistic response by exposure to metals and WSSV, because metals may affect the dynamic of disease transmission in aquaculture species (Liao et al, ).…”
Section: Discussionmentioning
confidence: 99%